Incorporating scale effect into a failure criterion for predicting stress-induced overbreak around excavations. (March 2020) - Delonca, A.; Vallejos, J.A.
Abstract: The evaluation of the depth of brittle failure around excavations is of major importance in order to optimize the design of underground excavations and ensure the safety of workers and equipment. The current proposed approaches to evaluate it are related to a single scale of study (intact rock or rock mass scale). Therefore, they are scale-dependent, and cannot be applied for all excavation diameter. In this paper, a generalized failure criterion including the scale effect for predicting stress-induced overbreak around excavations is developed. This failure criterion is based on the damage initiation relation ( σ 1 = Aσ 3 + Bσ c ). The scale effect is included into it through a relation proposed to evaluate the B parameter and depending on the scale of study. The fit parameters of the relation proposed have been defined considering a database at both rock mass and intact rock scales arising from a literature review. For intact rock scale, the B parameter is defined as a function of the diameter of the excavation, expressed following a potential form. For rock mass scale, the B parameter is defined equal to 0.35, regardless the diameter of the excavation. Based on the proposed B parameter relation, the depth and extension of the brittle failure around excavations can be evaluated for any scale of study. Highlights: A generalized failure criterion to predict overbreak around excavation is developed. It includes the scale effect and so can be used for any diameter of excavation. It uses the damage initiation relation (σ1  =  A σ3  +  B σc ) and defines the B parameter. For intact rock scale, B is function of the diameter following a potential form. For rock mass scale, the B parameter is equal to 0.35, for all diameter.